PENINGKATAN HASIL BELAJAR PKn MATERI GLOBALISASI MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION - Puji Astomo (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2018)
The purpose of this study is to improve student learning activities and learning outcomes of fourth grade students of SD Negeri Supenuh Sugio Subdistrict, Lamongan Regency on globalization material by applying the STAD type cooperative learning model. This classroom action research is carried out in two cycles, each consisting of four stages: planning, action, observation, and reflection. The subjects in this study were fourth grade students of SD Negeri Supenuh. Data collection techniques used are test and non-test techniques. Data analysis was carried out by analyzing qualitative and quantitative data. Based on the implementation of the first cycle student learning activities reached 65.12% and in the second cycle increased to 79.87%. In the first cycle, the average value of student learning outcomes reached 70.67 with a complete percentage of classical learning of 66.67%. Meanwhile, in the second cycle the average value of student learning outcomes increased to 81.67 with a complete percentage of classical learning at 93.33%.